1989
DOI: 10.1520/jfs12753j
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Radiocarbon (14C) to Identify Human Skeletal Materials of Forensic Science Interest

Abstract: The radiocarbon (14C) method is a well-known isotopic dating technique by which age can be assigned to organic materials, including human bone. Natural and anthropogenic anomalies in 14C activity in the biosphere over the last few centuries, including the presence of artificial or “bomb” 14C after 1950, can be used as an isotopic tracer to assign human bone samples with high degrees of probability to one of three temporal periods within the recent past: a Non-modern period (before about A.D. 1650) of no forens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…At present, only isotope dating methods seem to provide valid information for the assessment of the postmortem interval (PMI) of skeletal human remains. These techniques are, however, expensive, and their reliability has so far only been tested on small samples [9,12,[16][17][18][19][20][21]. Recently, Verhoff and Kreutz systematically reviewed published, commonly used methods in their literature survey and, on the basis of their results, developed their own recommendations for a practical approach [3].…”
Section: Introductionmentioning
confidence: 99%
“…At present, only isotope dating methods seem to provide valid information for the assessment of the postmortem interval (PMI) of skeletal human remains. These techniques are, however, expensive, and their reliability has so far only been tested on small samples [9,12,[16][17][18][19][20][21]. Recently, Verhoff and Kreutz systematically reviewed published, commonly used methods in their literature survey and, on the basis of their results, developed their own recommendations for a practical approach [3].…”
Section: Introductionmentioning
confidence: 99%
“…This is achievable because it decays at a known, fixed rate and its levels can be related to the wellconstrained atmospheric nuclear weapons testing peak that sits above the natural production level. Taylor et al (1989) proposed that three time periods could be assigned to the recent past: (1) a pre-1650 period they termed "non-modern," (2) the period from 1650-1950 termed "pre-modern," and (3) a post-1950 period termed "modern." It could be argued that, more correctly, for forensic studies, pre-modern should be AD 1650 to 1955 and modern should be post-AD 1955 since it is only from post-1955 that fraction modern values >1 are observed and hence the remains can be unambiguously assigned to the modern period.…”
Section: Introductionmentioning
confidence: 99%
“…It could be argued that, more correctly, for forensic studies, pre-modern should be AD 1650 to 1955 and modern should be post-AD 1955 since it is only from post-1955 that fraction modern values >1 are observed and hence the remains can be unambiguously assigned to the modern period. Taylor et al (1989) demonstrated that in the absence of other information, use of single 14 C measurements on bone collagen from juveniles and adults can provide limited information, i.e. whether or not the person died during the nuclear era.…”
Section: Introductionmentioning
confidence: 99%
“…However, some civil cases may require further investigation with respect to identification. Analysis of radiocarbon content in bone and careful comparison with atmospheric radiocarbon bomb-curve values can aid in determining the forensic relevance by discriminating human remains from individuals who died before 1950 from those who were alive after that date 3e8 (Geyh, 2001;Taylor et al, 1989;Ubelaker, 2001;Ubelaker and Buchhoz, 2006;Ubelaker and Houck, 2002;Wild et al, 2000). Although establishing the date of death later than the mid-1950s may not ascertain the forensic interest of the finding, for example due to criminal injunction within the last 50 years, a pre-mid-1950s dating can usually rule out any forensic significance.…”
Section: Introductionmentioning
confidence: 99%